THE IMPLEMENTATION OF CADETS INNOVATION CREATION CORNER IN INCREASING CADETS’ SPEAKING ABILITY - Muhammad Sapril Siregar; Nanda Afra Kusturi; Diah Vitaloka Hartati (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2022)
This study aimed to figure out cadets responses toward the implementation of Cadets Innovation Creation Corner in increasing cadets speaking ability. The cadet corner is a place and activities for cadets to practice their speaking English based on their respective majors. The place includes nautical, engineering and electrical class. The activities that they do they will try to make a creation based on their major and try to explain it in English. The goal is that they get used to explaining the tools they use on the ship according to their field. this makes them accustomed to speaking in English and remembering vocabulary, working methods and tools they often use. The qualitative method was used to collect the data. The sample was the second-grade cadets of Merchant Marine Polytechnic of Malahayati, which consisted of 22 cadets. The open-ended questionnaire was distributed as the instrument for collecting the data. It consists of three questions that relate to cadets opinions on this strategy. The data was analyzed by using an interactive model. The result of this study indicated that there were positive responses of the cadets toward English Cadets Corner activity implementation in increasing their speaking ability. Most cadets consider this strategy was beneficial in supporting their speaking in English. The cadets opinions were categorized into agree and disagree group participants. The implementation of English cadets corner activities was very useful in increasing cadets speaking ability in English, especially about their major. Therefore, the other university could also use this strategy to support the cadets’ speaking ability in other genres of English.